2022
DOI: 10.1029/2022gl101117
|View full text |Cite
|
Sign up to set email alerts
|

Complex Crater Formation by Oblique Impacts on the Earth and Moon

Abstract: Impact craters are ubiquitous features on all solid solar system bodies. The final morphology of a crater depends on its size: small craters have simple, bowl-shaped cavities, while larger craters are subject to more profound late-stage, gravity-driven collapse, leading to complex morphologies including flat crater floors, central peaks or rings of peaks, and a terrace zone near the crater rim (e.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The crater is distinctly asymmetric with steeper rim faults and a deeper ring syncline in the northeast in comparison to the southwest. This is consistent with results of oblique impact experiments 24 , impact simulations 25 , and observations of con rmed impact craters 26 , which show that a deeper annular moat would be expected in the uprange direction. However, inherited and reactivated normal (or transtensional faults) add complexity to the interpretation, as the inherited structural fabric has a strong NW-SE fault orientation.…”
Section: Reconstructing Impact Anglesupporting
confidence: 90%
“…The crater is distinctly asymmetric with steeper rim faults and a deeper ring syncline in the northeast in comparison to the southwest. This is consistent with results of oblique impact experiments 24 , impact simulations 25 , and observations of con rmed impact craters 26 , which show that a deeper annular moat would be expected in the uprange direction. However, inherited and reactivated normal (or transtensional faults) add complexity to the interpretation, as the inherited structural fabric has a strong NW-SE fault orientation.…”
Section: Reconstructing Impact Anglesupporting
confidence: 90%
“…Crater-forming impacts involve high energy release with high temperatures and pressures across short time scales. Their structural and morphological characteristics depend on several interconnected factors, including the impact dynamics, target, and bolide characteristics and formations mechanisms, all of which are reflected in the wide range of craters observed in planetary bodies [51,52]. Note that Figure 7 also includes the reconstructed profiles from Collins et al [19], which showed that their reconstructed profiles were consistently above the actual postimpact topography observed in the field.…”
Section: Crater Surface Topographymentioning
confidence: 85%
“…Such difference might be caused by the difference in the mechanical premises between DEM and hydrocode-based modeling methods. Determining the impact angle and trajectory has been investigated from field observations and numerical simulations [13,18,19,51]. Crater-forming impacts involve high energy release with high temperatures and pressures across short time scales.…”
Section: Crater Surface Topographymentioning
confidence: 99%
“…Note that oblique impacts in the three-dimensional simulations may enlarge the melt volume within the methane clathrate layer (Wakita et al 2019(Wakita et al , 2022a. Nevertheless, their change in the topography might be modest (Davison & Collins 2022). As we focus on the crater size (diameter and depth), the fate of impact ejecta is also beyond the scope of our work.…”
Section: Discussionmentioning
confidence: 99%